Adherence to follow-up in women with cervical intraepithelial neoplasia grade 1 - Manasawee Srisuttayasathien; Tarinee Manchana (Elsevier, 2021)
Objectives: Adherence to follow-up is crucial for cervical intraepithelial neoplasia grade 1 (CIN1) because these women have a chance of progression to high-grade premalignant cervical lesions and cervical cancer. This study aimed to evaluate the rate of adherence to follow-up in women who were initially diagnosed with CIN 1 over a period of 24 months and to evaluate the regression and progression rate of CIN 1. Material and methods: Of 1050 women who visited a colposcopy clinic from October 2013 through March 2017, 138 with histologically proven as CIN 1 were recruited. Adherence to follow-up, the regression and progression rate of CIN 1 were retrospectively assessed. Results: Of the 138 women, 86 (62.3%) followed regularly until the study endpoint at 24 months. During the study period, 10 women received ablative treatment. The regression rate in women who had surveillance with cervical cytology was 69.7%, persistent disease of 18.4%, and progression to CIN 2-3 of 11.8%. In contrast, 80% of women who received ablative treatment had regression, 20% of them had persistent disease but none had progression. Conclusions: Nearly 40% of women with CIN 1 were lost to follow-up at 24 months. Adherence to the follow-up should be emphasized to all women. Intensive interventions to improve adherence and clinical outcome might be an option, particularly among women with poor compliance.